2016
DOI: 10.1590/s1679-45082016ao3490
|View full text |Cite
|
Sign up to set email alerts
|

Infections and systemic lupus erythematosus

Abstract: Objective To determine the incidence of infections in a population of systemic lupus erythematosus individuals and the characteristics of infections regarding original site, as well as to study the possible associations between infections and treatment.Methods An analytical retrospective study using data from medical charts of systemic lupus erythematosus patients from a single university hospital. A total of 144 patients followed up for five years were included. Data collected comprised age of patients and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
5
0
3
Order By: Relevance
“…Nevertheless, a recent study has shown that infections are a major cause of mortality in both early and late in the course of SLE. 35…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent study has shown that infections are a major cause of mortality in both early and late in the course of SLE. 35…”
Section: Discussionmentioning
confidence: 99%
“…The use of cyclophosphamide, prednisone and azathioprine has also been associated with herpes zoster infections. 23,27,28 In contrast, a previous study by Ruiz-Irastorza et al on the risks of infection among SLE patients has reported a 16-fold reduction in risk of major infection in patients prescribed with antimalarials namely hydroxychloroquine and chloroquine. This was supported by other studies by Siso et al (2008) and Bulthink.…”
Section: Management Of Sle Patients With Latent and Active Tb Infection Latent Tb Infectionmentioning
confidence: 84%
“…Even so, other studies have shown that the use of cyclophosphamide is associated with urinary tract infections, with haemorrhagic cystitis being one of the known complications of cyclophosphamide use. [23][24][25][26] Whereas, mycophenolate mofetil use has also been associated with cystitis, upper airway infection, bronchitis and cellulitis. The use of cyclophosphamide, prednisone and azathioprine has also been associated with herpes zoster infections.…”
Section: Management Of Sle Patients With Latent and Active Tb Infection Latent Tb Infectionmentioning
confidence: 99%
“…30 Cyclophosphamide is a cytotoxic alkylating medication that interferes with lymphocyte proliferation, reducing the production of effector and cytotoxic T cells, as well as autoantibody production. 31 The response of cytotoxic T lymphocytes is crucial for viral eradication in COVID-19. Patients with severe forms of COVID-19 present with perivascular lymphocytic infiltrates and the depletion of almost all T-cell subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Cyclophosphamide reduces antibody production, thus also interfering with the humoral response to the virus. 31 The COVID-19 Global Rheumatology Alliance also observed worse outcomes in patients with SLE and COVID-19 who were on cyclophosphamide treatment. 32 The present study did not observe worse outcomes in patients treated with rituximab, as reported by some studies.…”
Section: Discussionmentioning
confidence: 99%